2012
DOI: 10.3988/jcn.2012.8.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Weekend Admission in Patients with Acute Ischemic Stroke Is Not Associated with Poor Functional Outcome than Weekday Admission

Abstract: Background and PurposeStroke requires consistent care, but there is concern over the "weekend effect", whereby a weekend admission results in a poor outcome. Our aim was to determine the impact of weekend admission on clinical outcomes in patients with acute ischemic stroke in Korea.MethodsThe outcomes of patients admitted on weekdays and weekends were compared by analyzing data from a prospective outcome registry enrolling 1247 consecutive patients with acute ischemic stroke admitted to four neurology trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Data on quality of care on weekends are heterogeneous. Most studies demonstrate a poorer quality of care, and negative effects for patients being admitted on weekends [ 18 21 ], whereas others do not confirm these findings [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on quality of care on weekends are heterogeneous. Most studies demonstrate a poorer quality of care, and negative effects for patients being admitted on weekends [ 18 21 ], whereas others do not confirm these findings [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, it was found that a longer time period from admission until the next WHs was related only to mRS score 0–1, but not related to mRS score 0–2 or death at three-months on multivariate analysis. Since previous studies selected mRS score 0–1 at discharge or mRS score 0–2 and mortality at three-months as indicators of patient outcomes (Table 4) (13,6,8,9,1119), it was difficult to compare the present results with them. The explanation for the present results is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Another possible explanation is that stroke type, specifically ischemic stroke only, affected the negative results for the outcome of mRS score 0–2 or mortality. It has been reported that the absolute effect of off-hours admission was stronger in hemorrhagic stroke than in ischemic stroke (4), and most of the studies that focused on ischemic stroke did not find a significant weekend effect (Table 4) (1317).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations